Molecular characterization of plasmid-mediated AmpC beta-lactamase- and extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae among corvids (Corvus brachyrhynchos and Corvus corax) roosting in Canada. Issue 11 (23rd August 2018) - Jamborova, Ivana; Janecko, Nicol; Halova, Dana; Sedmik, Jiri; Mezerova, Kristyna; Papousek, Ivo; Kutilova, Iva; Dolejska, Monika; Cizek, Alois; Literak, Ivan
ABSTRACT: This study evaluated the carriage of AmpC and extended-spectrum beta-lactamase (ESBL) genes and associated plasmids in faecal bacteria of Canadian corvids. Faecal samples from 449 birds in five roosting sites across Canada were analyzed using selective media, screening for AmpC and ESBL genes by PCR, and sequencing. Genomic relatedness was determined by PFGE and MLST. Plasmid mobility was studied by conjugation and transformation experiments, followed by plasmid typing. In total, 96 (21%, n = 449) cefotaxime-resistant Escherichia coli and three (0.7%) Klebsiella pneumoniae isolates were identified. ESBL genes bla CTX-M-1 (n = 3), bla CTX-M-14 (n = 2), bla CTX-M-32 (n = 2) and bla CTX-M-124 (n = 1) were detected in eight E. coli isolates, whereas bla SHV-2 (2) was found in two K. pneumoniae. E. coli isolates contained bla CMY-2 (n = 83) and bla CMY-42 (n = 1). The high genetic diversity of the isolates and presence of clinically important E. coli ST69 (n = 1), ST117 (n = 7) and ST131 (n = 1) was revealed. AmpC genes were predominantly carried by plasmids of incompatibility groups I1 (45 plasmids), A/C (10) and K (7). The plasmid IncI1/ST12 was most common and found in diverse E. coli STs in all sites. Highly diverse E. coli isolates containing AmpC and ESBL genes, including clinically important clones and emerging plasmids, are in circulation throughout Canadian wildlife. Abstract : Highly diverse population of E. coli, including resistant pathogenic strains of public health concern carrying plasmids with resistance genes of significance are in circulation in Canadian wildlife.